Operational optimization for part-load performance of amine-based post-combustion CO2 capture processes. (1st March 2018) - Oh, Se-Young; Kim, Jin-Kuk
Abstract: It is typical to assume that the capture system operates at the full working load of the power plant. This study aims to develop systematic design framework which can provide a cost-effective strategy for operating CO2 capture plant under different operating load. The part-load performance of CO2 capture process together with power plant is modeled and evaluated with a process simulator UniSim ® . This study considers both natural gas-fired combined cycle (NGCC) and coal-fired plants, in which optimization is carried out for finding an economic operating strategy to minimize regeneration energy without compromising process efficiency of the capture system. The multi-period modeling approach is applied to accommodate discontinuous nature of part-load performance, with which techno-economic impacts of part-load operation is investigated in a holistic manner. The case study is presented to demonstrate the usefulness of proposed design and optimization framework and to provide practical guidelines and conceptual insights for part-load operation in practice. From the case study, the specific reboiler duty is reduced through the superstructure optimization at full-load operation, which is about 3% lower than one without structural modifications. Also, the operational optimization for part-load achieves energy savings by 2–3% in NGCC and 3–5% in coal-fired power plant. Highlights: Operational optimization of amine-based CO2 capture plant at part-load. Consideration of multiple structural modifications for energy savings. Investigation of techno-economic impacts of part-load operation.